If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.72 + -2x = 2x + x Combine like terms: 2x + x = 3x 0.72 + -2x = 3x Solving 0.72 + -2x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 0.72 + -2x + -3x = 3x + -3x Combine like terms: -2x + -3x = -5x 0.72 + -5x = 3x + -3x Combine like terms: 3x + -3x = 0 0.72 + -5x = 0 Add '-0.72' to each side of the equation. 0.72 + -0.72 + -5x = 0 + -0.72 Combine like terms: 0.72 + -0.72 = 0.00 0.00 + -5x = 0 + -0.72 -5x = 0 + -0.72 Combine like terms: 0 + -0.72 = -0.72 -5x = -0.72 Divide each side by '-5'. x = 0.144 Simplifying x = 0.144
| -0.25c+20.5=12.9 | | E/9-5=-11 | | 8x-2-4x=-12 | | E/9-5=-5 | | 5x/3+3=x+7 | | -0.25c+20.5= | | 1.5(9b-27)=36 | | 1=y(4x+1) | | 0.20+0.35(50)=31.5 | | 2x+1=13-x | | -4(2t+7)=-44 | | 2x-7y=11fory | | 4x+7=-4x+20 | | -12x+12x+8=16 | | T-15=76 | | 6y+-15=9 | | 7=-7-(p-8) | | 8x+0.5=7x+2 | | 2m+13=25 | | 19m+9n=16 | | 2x+4=4x+16 | | 5x+12=-42-4x | | 9=q-4 | | 5(f-9)=-45 | | n/3-6=10 | | 4x+5=-2+2 | | 9=a-4 | | 8(s-6)=-100 | | y/-23 | | 2(x^2+4)=0 | | 2P(A)=P(B)=5/13 | | 64p=16 |